(untitled) (Philologia, 2021)
The Sun Goddess Amaterasu is the principal kami of the Shinto pantheon and, at the same time, ancestor of the imperial dynasty. Ancient Japanese animistic beliefs presupposed the existence of Kami (‘god’, ‘spirit’), but later this original mythology was organized under the term ‘Shinto’ − a religion created in response to the new upcoming religion of Buddhism. This paper deals with the concept of the Sun Goddess, the central ﬁgure of the Japanese mythology, who was accepted by the ruling dynasty as their god-ancestor and god-protector, most probably for political reasons, in order to ensure their historical dominance in the region. Therefore, we will demonstrate the meaning of the kami concept, and provide a short history of Shinto development and the place Amaterasu holds in Japanese religious as well as political and social life, in ancient and modern-day Japan.